"TUGAS ADMINISTRATIF TENAGA KEPENDIDIKAN NON-GURU: PENERIMAAN DAN TANTANGAN" - Bucoy, May Lanie; Punzalan, Randy D. (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
This study aimed to assess the level of acceptance and coping mechanisms of non-teaching personnel in handling administrative tasks in public elementary schools under the Division of Cabuyao, in line with DepEd Order No. 2, s. 2024. It sought to determine how non-teaching personnel accept these added responsibilities and how they manage related challenges. Research method uses a mixed-method explanatory design, involving 10 non-teaching personnel assigned to administrative duties. Data were collected through a survey-questionnaire for the quantitative phase and interview guide questions for the qualitative phase. Quantitative data were analyzed using statistical tools, while qualitative data were examined using QDA Miner and reviewed by a qualitative analyst. Findings revealed that non-teaching personnel generally accepted their new roles but faced significant challenges such as limited skills, lack of training, and minimal support from former coordinators. These difficulties often led to psychological and emotional stress. From their experiences, four key themes emerged: (1) Acceptance amidst uncertainty, (2) Struggles with time and workload, (3) Fear of inadequacy, and (4) Transition difficulties due to limited preparation. In terms of coping, they developed mechanisms like (5) Peer support and self-learning, (6) Improved time management, (7) Collaboration, and (8) Seeking mentorship. Based on the findings, the study recommends the implementation of Programs, Projects, and Activities (PPAs) under a Personnel Management Plan to support non-teaching personnel in fulfilling administrative roles. School heads and teachers are encouraged to provide regular monitoring, technical assistance, and mentoring to ensure successful role adaptation and effective task execution.